Air travel as a risk factor for introduction of measles in a highly vaccinated population - van Binnendijk, Robert S.; Hahné, Susan; Timen, Aura; van Kempen, Gijs; Kohl, Robert H.G.; Boot, Hein J.; Wolthers, Katja C.; Wetsteijn, José C.F.M.; de Vries, Anne; Westert, Krista; Brown, Kevin E.; de Swart, Rik L. (Vaccine, 2008)
Epidemiological and molecular investigation of two small measles clusters in The Netherlands in July/August 2007 revealed an association with travel by air of the index cases and nosocomial spread in the first cluster. Although these importations did not result in an outbreak among unvaccinated subjects, the observations illustrate the challenges for measles control in a country with high measles vaccination coverage (>95%) but with pockets of low coverage.